Teachers' Demographic Factors Influencing Their Attitudes Towards Education of Students with Learning Disabilities in Regular Classrooms in Ibadan, Nigeria - Kelechi Uchemadu Lazarus (Indonesian Journal of Disability Studies, 2020)
The study investigated the level of attitudes towards the education of students with learning disabilities among teachers in regular education classrooms. It also examined the influence of four teachers' demographic factors on their attitudes towards education of students with learning disabilities in regular classrooms Ibadan, Nigeria. The descriptive research design was adopted for the study whilst the multi-stage sampling procedure was adopted to select the study sample. A total of 125 teachers participated in the study, 64 (51.2%) were males whilst 61 (48.8%) were females. A self-designed questionnaire tagged Teachers' Attitude towards Education of Students with Learning Disabilities in Regular Education Classrooms (TAESLDRECQ) with a reliability of 0. 81 was utilized to collect data. One research question and four hypotheses were generated and tested. Percentage, mean, standard deviation, t-test and Analysis of variance (ANOVA) statistics were employed to analyze the data generated from the participants at 0.05 level of significance. Whilst the result of the research question reveals a grand mean of 2.59 which is slightly higher than the criterion mean of 2.50, the result from the test of norm showed that 9.6% (n=12) teachers had negative attitude, whilst 90.4% (n=113) teachers had positive attitude. Therefore, it was concluded that there is a positive attitude towards education of students with learning disabilities in regular education classrooms. The results shows that teachers' attitudes towards education of students with learning disabilities in regular education classrooms based on: gender (Crit-t = 1.96, Cal.t = 1.440, DF = 123; educational qualification (F = 1.630, p(.171)>.05); years of experience (F = 2.329, p(.102)>.05); and category of students taught which could be either junior secondary or senior secondary class (Crit-t = 1.96, Cal.t = .035, DF = 123, p(0.973) towards education of students with learning disabilities in regular education classrooms. Hence, it was concluded that teachers' attitude towards education of students with learning disabilities is the same irrespective of their gender, educational qualification, years of experience and category of student taught (either junior secondary or senior secondary class). On the basis of these findings, it was recommended that there should be more trainings and in-service professional development programmes such as orientation, workshops, seminars, conferences to allow teachers in regular education classrooms to acquire knowledge, skills and values required for the adequate education of students with learning disabilities in their classrooms.